Método da superposição modificado como uma nova proposta de atribuição de responsabilidades sobre distorções harmônicas - Santos, Ivan Nunes (2011)
Guidelines provided by the Brazilian Electricity Distribution Agency and the National Operator Grid considers, amongst other power quality indicators, issues associated to harmonic distortions. Such documents, as far as harmonics are concerned, are focused to different goals such as definitions, measurement procedures, reference values, etc. Having in mind these orientations and by recognizing that mitigation techniques to adequate the harmonic levels to the recommended values are frequently linked to high costs emerges the necessity of ways to find, at a given PCC, the harmonic distortion percentile due to the utility and the consumer itself. Within this context, a few publications have attempted to provide means to share the responsibility upon a measured voltage distortion and, usually, the approaches are based on frequency domain procedures and superposition principles. These have shown to be promising but the final methodology is still to be fulfilled. Although the simplicity of such approaches it has been found that the difficulties at obtaining the required supply system and consumer equivalent harmonic impedance are quite limiting to the use of such strategies. Aiming at achieving a manner of overcome such matters emerges this thesis which context is dedicated to the search of a systematic manner of sharing the responsibilities for a given busbar distortion. The work is then developed towards the investigation of the current methods limitations and inaccuracy and to propose a new mechanism that allows for attributing the percentile origin of the distortions. This has been called by Modified Superposition Method and its fundamentals, procedures, computational results, etc. are fully described in the work.